ANALISIS PERCAKAPAN DALAM ACARA â€œTALK SHOW KICK ANDY DENGAN PENGARANG NOVEL NEGERI LIMA MENARAâ€ - zulfatun anisah (AN-NAS, 2018)
ABSTRACT The conversation analysis contained in the Kick Andy Talk Show video contains four subjects, including conversation topics, conversation structure, conversation conversation, and conversational discourse. On the topic of conversation found three topics, namely general topics, sustainable topics and real topics. Furthermore, in the conversation structure found conversation topics found at the beginning of the conversation, the conversation's core, and the end of the conversation. As for the conversational speech, there are two types of speech conversations. First off said with the turn set, the second instead of talking with automatic turn. The last analysis of conversation is the conversation discourse. The unity is shown in the cohesion and coherence that exists in the content of the conversation from beginning to end of conversation.